Business feasibility analysis of purse seine at Fish Auction Place (Tempat Pelelangan Ikan/TPI) Kranji, Lamongan - Romadoni, Nadia Vika; Sawiji, Asri; Muslih, Toha (Journal of Marine Resources and Coastal Management, 2022)
Lamongan Regency is one of the districts in East Java which have high potential of fishery resources. Purpose of this study is to determine the business feasibility of purse seine fishing gear at TPI Kranji, Lamongan. The data collection technique was carried out by field observations and in-depth interviews. Methods of data analysis with financial analysis using Net Present Value (NPV), Payback Period (PP), and Benefit Cost Ratio (B/C Ratio) methods. Analysis results shows that the purse seine business at TPI Kranji was financially feasible according to the NPV value at the 5th year of IDR 1,890,298,600. The purse seine business at TPI Kranji also can return the initial investment costs in a period of 1 year based on the PP calculation and the B/C Ratio value is obtained 22.49 so it is classified as financially feasible. It is recommended that fishing business using purse seines at TPI Kranji is not only an effort to get the maximum profit, but also to maintain the sustainability of fisheries in a sustainable manner.